The Influence of the Use of Capcut-Based Learning Videos on the Learning Outcomes of Fine Arts Students in Class VIII Of SMP Negeri 2 Baranti - Selvia Saprul; Abd. Kahar; Syamsunir; Usman M; Sam Hermansyah (MultiTech Publisher, 2024)
This research aims to determine the effect of Capcut-based learning videos on class VIII students' fine arts learning outcomes at SMP Negeri 2 Baranti. This research uses a Quasi-Experimental type of research. The sample from this research was class VIII B, totaling 26 students. Tests and documentation are the methods used in this research to obtain data. The data analysis technique in this research uses the mean formula. Based on research, according to hypothesis testing through data analysis, the initial test score (Y) was lower than the final test score (X), namely Y=53.07 < X=85.19. The difference in the results proves that the alternative hypothesis (Ha) which states that there is an influence of the use of Capcut- based learning videos on the Fine Arts learning outcomes of class VIII students at SMP Negeri 2 Baranti is